Sebuah Penelitian Tentang Pan-Sensualisme Sebagai Bentuk Silang Budaya: Karya Seni Oleh Jim Supangkat; Ken Dedes (1975) - Aprilia Ariesty Wibowo; Kiki Rizky Soetisna Putri; Irma Damajanti (Journal of Visual Art and Design, 2023)
This study examined the use of the term ‘Pan-Sensualism’ in the discourse on contemporary Indonesian new art and how this manifested itself in artworks created at the beginning of the Indonesian New Order era (1966-1998). Jim Supangkat was one of the artists and initiators in forming the artist group Gerakan Seni Rupa Baru Indonesia (Indonesian New Art Movement), which then organized the first Seni Rupa Baru 75 exhibition in 1975. Jim Supangkat presented six installation works with different narratives, but Ken Dedes was the only one that presented the dialectic of traditional and modern culture. The Prajnaparamita, or Ken Dedes statue is presented with a drawing of the body of a woman wearing jeans with the buttons open. In looking at the formal, social-historical, cultural, feministic, and other elements in the work of Ken Dedes (1975-1996), we used the iconographic research method. This method helps to see several aspects of Supangkat’s visual works related to the aesthetic paradigm of Pan-Sensualism and the intersection of two cultural elements, i.e., high and low art, which may be distinguished based on social class appreciation.